Relationships Among Dispositional Mindfulness, Distress Tolerance, and Women's Dating Violence Perpetration: A Path Analysis. Issue 14 (July 2019) - Brem, Meagan J.; Khaddouma, Alexander; Elmquist, Joanna; Florimbio, Autumn Rae; Shorey, Ryan C.; Stuart, Gregory L.
Scant research examined mechanisms underlying the relationship between dispositional mindfulness and dating violence (DV) perpetration. Using a cross-sectional design with 203 college women, we examined whether distress tolerance mediated the relationship between dispositional mindfulness and DV perpetration (i.e., psychological aggression and physical assault). Path analyses results revealed indirect effects of mindfulness facets nonjudging of inner experiences and nonreactivity to inner experiences on both psychological aggression and physical assault through distress tolerance. Mindfulness facets observing, describing, and acting with awareness were not linked to DV perpetration through distress tolerance. Results suggest that women who allow internal experiences to come and go without assigning criticism or avoidance are better able to tolerate transient distress and less likely to abuse a dating partner. Future research may examine distress tolerance and dispositional mindfulness facets as potential intervention targets for women who abuse dating partners.